The tournament - Mohamad Azmin, Nur Azwani; Abdul Talib, Nurafida; Ngah, Nazlin Emieza; Adenan, Nur Dalila; Abdullah, Nasiha (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
The target stands in the distance. A challenge to be conquered by all. The archers take heir turns in reticence. Their arrows flying, straight and tall.